A facile and simple method for synthesis of graphene oxide quantum dots from black carbon - Lu, Qiujun; Wu, Cuiyan; Liu, Dan; Wang, Haiyan; Su, Wei; Li, Haitao; Zhang, Youyu; Yao, Shouzhuo (Green chemistry : an international journal and green chemistry resource : GC, 2017)
Synthesis of graphene oxide quantum dots (GO-dots) often requires strong concentrated acid, and takes a long time. Herein, we used black carbon as a precursor and H 2 O 2 as a facile oxidant and developed a simple and facile one-pot hydrothermal method for synthesis of GO-dots without the need to use strong concentrated acid and the entire synthetic process only took 90 min. Furthermore, any other post-processing steps are avoided.